Management of the Process of R & D Cost Formation in State Scientific and Educational Institutions - O. V. Losevaa; T. V. Tazikhina; M. A. Fedotova (Управленческие науки, 2019)
Management of the process of research and development cost formation (hereinafter — R & D) in Russian scientific organizations and institutions of higher education is an urgent task in an environment where budget funding for research is reduced, and the universities themselves are interested in increasing their revenues from fundamental, applied research and experimental development. In addition, the rating of educational institutions, their competitiveness in the market of intellectual services, including, depends on the number of successfully implemented together with business partners of innovative projects that are based on research and development, the number of commercialized results of intellectual activity (hereinafter-R&D) and concluded state contracts. Methods of algorithmization, modeling, calculation coefficients, expert estimates, determination of the initial (maximum) price of the contract have been used. Research result: Two models of research performance cost formation by the educational and scientific organizations are presented: 1) on the state task; 2) on other types of R&D. In the first case, the model is based on the allocated subsidy for the implementation of the state task, adjusted for the coefficient of labor intensity increase, which is calculated on the basis of the criteria of scientific, technical and consumer efficiency of research. The final labor intensity increase coefficient is a rating of the application of a particular creative team to perform research. In the second case, the fundamental element of value formation is the initial (maximum) price of the contract, which can be determined on the basis of cost, comparative or income approach, as well as (in the case of the state customer) by summing tax revenues to the budgets of all levels from the production and sale of high-tech products. The total value is defined as the minimum value of the contract prices calculated by different methods. The developed models of value formation can be used to build a methodology for determining the cost of R&D